A characterization for the degree of Fano varieties - Đặng, Tuấn Hiệp (2023)
Using a recent result on intersection numbers over Grassmannians, we propose a characterization for the degree of Fano varieties of linear subspaces on complete intersections in terms of the coefficient of a symmetric polynomial.